Improving Hepatitis C Screening Rates in Primary Care. (4th October 2017) - Ajmal, Saira; Jagtiani, Anil; Thoendel, Matthew; Mahmood, Maryam; Chaudhry, Rajeev; Franqueira, Andrew; Whitaker, Jennifer
Abstract: Background: Hepatitis C virus (HCV) is the most common chronic blood-borne pathogen in the US. It is the leading cause of complications from chronic liver disease and the most common indication for liver transplants among US adults. National guidelines recommend one-time birth cohort based screening for adults born from 1945 to 1965 regardless of risk factors for blood-borne infections. A magnitude assessment of infectious disease outpatients demonstrated a birth cohort based screening rate of 38%. Prior quality improvement projects at other institutions have resulted in significant improvements in screening rates, with up to 90% of eligible individuals being screened. We aim to increase HCV screening by 20% amongst Primary Care Internal Medicine (PCIM) patients born from 1945 to 1965 at Mayo Clinic Rochester over a 6 month period. Methods: The baseline screening rate over a 2-year period (January 1, 2015–December 31, 2016) was extracted from medical records. An anonymous online survey was created and sent to PCIM providers to assess their comfort with screening guideline recommendations and current perceived practices, as well as perform a stakeholder analysis to identify current barriers to screening. A reminder email was sent 3 weeks after the initial invitation. Results: The baseline screening rate was 6% (769 of 12, 269 eligible visits). We attained a 30% (17/57) survey response rate after 4 weeks. Only 6% (1/17) reported screening all patients based on guideline recommendations. We found that 35% of providers are unsure who is eligible for screening. The majority (56%) cited not remembering to discuss screening, and only 18% felt very confident with their understanding of the guidelines. Other reasons for not screening per Figure 1. All providers stated they would screen more patients if there was a screening prompt, and 71% felt that providers needed more education. Conclusion: Based on the results we implemented an electronic medical record tool to prompt providers to order HCV screening on patients eligible by birth cohort, who had not been previously screened, and did not have known HCV infection. Education was provided via a divisional newsletter. We are currently collecting data to analyze screening rates 6 months after implementation of our intervention. Disclosures: All authors: No reported disclosures.